Multicultural Policy in Madrasah: Building Harmony and Tolerance in Islamic Education - Zamroni, Zamroni; Fajri, Muhamad (JURNAL AL-TANZIM, 2023)
This research aims to analyze the process of formulating and implementing madrasah policies in East Kalimantan. The madrasah in question is upper secondary level, or called MAN. The research objectives were achieved through phenomenological methods, descriptive approaches and interactive data analysis techniques, while data sources were obtained through documentation, interviews and observation techniques. This research concludes that there is a process of stratification of students' learning abilities and interests, not background segments. The legitimation process is marked by alignment with the vision and mission of the madrasah, as well as being in line with the policies of the Ministry of Religion. The allocation process involves determining time and location, such as allocating extracurricular activities related to arts and culture and the percentage of multicultural content in social and religious science subjects. The implications of the results of this research can be a reference for further research and practically a reference for policy-making to support the strengthening of multicultural education.